Nailfold Capillaroscopy in 430 patients with Rheumatoid Arthritis - Alireza Rajaei; Pooneh Dehghan; Ali Amiri (Babol University of Medical Sciences, 2017)
Background: Microvascular changes are one of the first obvious steps in numerous inflammatory diseases such as rheumatoid arthritis (RA). Nailfold video capillaroscopy (NFC) is an easy, reliable and safe method for evaluating peripheral microangiopathy. The objective of this study was to examine nailfold microcirculation in RA patients, assess morphological and structural changes quantitatively and qualitatively, and recognize useful changes. Methods: A total of 430 patients diagnosed with RA were examined in a period of 4 years. NFC was performed on all fingers of both hands in each patient. Different parameters indicating microvascular changes were detected and analyzed; such as microvascular architecture, capillary distribution disturbances, capillary morphology, capillary density, efferent/afferent limb ratio, subpapillary venular plexus and morphological abnormalities. The obtained results were categorized into normal pattern, nonspecific morphological abnormality and scleroderma pattern. Results: The mean age of participants was 51.03±14.54 (19-87 years) that consisted of 359 females and 71 males. Based on the findings, angiogenesis (74.7%) was the most pathological condition observed after tortuosity (99.5%). 7.2% and 20.9% of patients were categorized into normal and scleroderma pattern group, respectively. Among morphological abnormalities, angiogenesis, isolated enlarged loop, irregular enlarged loop and architectural derangement were significantly more frequent in scleroderma than normal pattern (p<0.001). Conclusion: NFC may play an important role in monitoring RA disease and patients’ follow-up. Therefore, in our opinion it could be considered in the course and follow-up of rheumatoid arthritis.